Molecular Confirmation of the Causative Agents of Diarrhea and Its Antimicrobial Susceptibility Tests - Enkhbayar, Enerel; Baatar, Narangerel; Amgalanbaatar, Avarzed; Ravjir, Oyungerel (Central Asian Journal of Medical Sciences, 2023)
Objectives: This study aimed to investigate molecular confirmation of the causative agents of diarrhea and its antimicrobial susceptibility tests in the samples collected from patients who have symptoms of diarrhea. There is a relative lack of diagnostic studies on the causative agents of diarrhea in Mongolia, especially on the causative agents of bacterial diarrhea and their antibiotic susceptibility. Methods: A rectal swab and stool sample were taken from 187 patients admitted to the NCCD Mongolia with a diagnosis of diarrhea and infection between June 2018 and April 2020 using a hospital-based instantaneous survey model, and bacteriology, molecular biology, and antibiotic susceptibility testing were performed at the laboratory of Bacteriology and Immunology, Institute of Veterinary Medicine. Results: Of the 187 samples, N=127 (67.9%), p<0.01) were confirmed by simple and multiplex PCR, and Salmonella spp., Shigella spp., E.Coli, and S.aureus were detected in n=20 (15.7%), n=16 (12.6%), n=20 (15.7%), and n=7 samples (5.5%), respectively. Multiplex PCR 3 samples did not detect the 16s rRNA gene of Campylobacteraceae and C.jejuni or cdt C gene of C.coli, all of which were negative. Therefore, multiplex PCR was performed for foursamples to detect pathogenic bacteria, and samples were E. coli positive but not campylobacter, salmonella, and shigella. Conclusion: 126 (67.4%) children aged 1-5 years were the most affected by foodborne infection, and most of the diarrhea causative agents detected were Salmonella spp, Shigella spp, E.Coli, and S.aureus.